2023
DOI: 10.1002/uog.26164
|View full text |Cite
|
Sign up to set email alerts
|

Fetal endoscopic tracheal occlusion for congenital diaphragmatic hernia: systematic review and meta‐analysis

Abstract: What are the novel findings of this work?There is an ongoing debate regarding whether the impact of fetal endoscopic tracheal occlusion (FETO) varies in severe and moderate congenital diaphragmatic hernia (CDH). We demonstrate that FETO is associated with a reduction in mortality, rate of pulmonary hypertension and use of extracorporeal membrane oxygenation (ECMO) in severe CDH, but reduces only mortality in moderate CDH. In addition, FETO is associated with late preterm birth (but not extreme prematurity) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Contrary to the previously published meta-analysis that included RCTs with mixed left- and right-sided CDHs [ 20 ], our meta-analysis employed the IPD restricted to patients only with left-sided and severe CDH. This is important when providers counsel their patients because the survival rates with FETO compared to expectant management are different between right- and left-sided CDHs; the survival rates for right-sided CDHs and left-sided CDHs are also different [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the previously published meta-analysis that included RCTs with mixed left- and right-sided CDHs [ 20 ], our meta-analysis employed the IPD restricted to patients only with left-sided and severe CDH. This is important when providers counsel their patients because the survival rates with FETO compared to expectant management are different between right- and left-sided CDHs; the survival rates for right-sided CDHs and left-sided CDHs are also different [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two randomized controlled trials (RCTs) suggested the potential benefits of FETO in improving postnatal survival for severe CDH [15,19]. Such results have also been confirmed in two meta-analyses [20,21]. In addition, FETO has been associated with perinatal complications such as preterm delivery and premature rupture of the membranes [22,23].…”
Section: Introductionmentioning
confidence: 89%
“…Two recently published randomized controlled trials by Deprest et al 2,9 ,. and a subsequent systematic review 3 investigating the effect of FETO on survival‐to‐discharge, showed promising results. However, the studies also showed a clear downside to the intervention: a steep increase in the risk of preterm prelabor rupture of the membranes (PPROM), defined as amniotic sac rupture prior to 37 weeks' gestation and before the onset of labor, in the FETO group compared with the expectant‐care group.…”
Section: Introductionmentioning
confidence: 99%
“…Surviving infants require intensive treatment and suffer from long-term sequelae. Recent evidence showed that fetal endoscopic tracheal occlusion (FETO) is beneficial for fetuses with CDH 2,3 .…”
Section: Introductionmentioning
confidence: 99%